IMPLEMENTASI FUNGSI MANAJEMEN PENDIDIKAN DALAM MASA PANDEMI COVID 19 - Muhammad Daud; Dg Mapata (LPPM Universitas Muhammadiyah Bulukumba, 2021)
The implementation of face-to-face learning is carried out in a limited manner with a sip system in every two-week inter-study day at this school. This type of research is a descriptive research that is evaluative in nature with the reason that the consideration of energy, thoughts, funds and time is very limited. Then the data is processed and analyzed objectively by combining the program and the implementation of learning during Covid 19. The findings of the analysis of educational management functions during the Covid 19 pandemic at the UPT-SPF of SMP Negeri 9 Bulukumba, Bulukumba district, which includes planning, organizing, implementing and monitoring that still pays attention to and establishes health protocols in schools handled by the Covid 19 task force. Then analyzed the implementation of education management functions during the Covid 19 pandemic at UPT-SPF SMP Negeri 9 Bulukumba, Bulukumba Regency. Analysis of the implementation of education management functions during the Covid 19 pandemic at UPT-SPF SMP Negeri 9 Bulukumba, Bulukumba Regency, prioritizing the safety of the soul and body of students so that they are not exposed to Covid 19.